Operative management of unstable sternal fracture in polytrauma: a case report and literature review - Andrikopoulou, Chrysa; Selmani, Edvin; Leivaditis, Vasileios; Antzoulas, Panagiotis; Tasios, Konstantinos; Liolis, Elias; Antzoulas, Andreas; Litsas, Dimitrios; Papadopoulos, Panagiotis Dimitrios; Theofanis, George; Nikolakopoulos, Konstantinos; Panagiotopoulos, Ioannis; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2026)
Sternal fractures are uncommon but clinically relevant injuries, most often resulting from blunt thoracic trauma in motor vehicle collisions. While most isolated fractures can be treated conservatively, surgical stabilisation may be required in cases of displacement, instability, or polytrauma. Modern plating techniques offer biomechanical advantages over traditional wire fixation, but indications remain variably defined. We report the case of a 33-year-old male polytrauma patient involved in a high-impact motor vehicle accident. He sustained a displaced sternal fracture with manubriosternal dislocation, bilateral rib fractures (right 4th–8th, left 6th–7th), flail chest, pulmonary contusion, a retrosternal haematoma, and left hip dislocation. Surgical management included open reduction and internal fixation of the sternum with 2 titanium plates, haematoma evacuation, and orthopaedic intervention. The postoperative course was initially uneventful; however, the patient was readmitted 1 month later with a surgical site infection caused by Proteus mirabilis.